ELECTRE-Based Decision Support Model for LPG Base Location Optimization - Putri, Ida Ayu Putu Calista Kencana; Sudipa, I Gede Iwan; Ariana, Anak Agung Gede Bagus; Yanti, Christina Purnama; Ekayana, Anak Agung Gde (Politeknik Ganesha Medan, 2026)
The kerosene to LPG (Liquefied Petroleum Gas) 3 kg conversion program since 2007 has successfully improved household energy efficiency, but equitable access to bases in remote areas is still an obstacle. In Tabanan Regency, Bali, eight villages do not have access to 3 kg LPG bases, making it difficult for the community to obtain LPG at the Highest Retail Price (HET) and timely supply. This research develops a decision-making model using the ELECTRE method to recommend optimal base locations based on a case study of four villages: Pupuan Sawah, Dalang, Mundeh, and Belatungan. The model integrates 15 criteria including population density, infrastructure accessibility, existing base distance, and the presence of public facilities with a multi-stakeholder approach. The model is expected to be a tool for LPG agents and policy makers in determining the optimal base location and supporting equitable distribution of subsidized energy.